Clitorienolactones and isoflavonoids of Clitorea ternatea rootsalleviate stress-like symptoms in reserpine-induced zebrafish model - Ngadni, Muhammad Afiq; Akhtar, Muhammad Tayyab; Ismail, Intan Safinar; Norazhar, Anis Irfan; Lee, Soo Yee; Maulidiani, Maulidiani; Shaari, Khozirah (Multidisciplinary Digital Publishing Institute, 2021)
Clitorea ternatea has been used in Ayurvedic medicine as a brain stimulant to treat mental illnesses and mental functional disorders. In this study, the metabolite profiles of crude C. ternatea root extract (CTRE), ethyl acetate (EA), and 50% aqueous methanol (50% MeOH) fractions were investigated using ultrahigh-performance liquid chromatography–diode array detector–tandem mass spectrometry (UHPLC–DAD–MS/MS), while their effect on the stress-like behavior of zebrafish, pharmacologically induced with reserpine, was investigated. A total of 32 compounds were putatively identified, among which, a series of norneolignans, clitorienolactones, and various flavonoids (flavone, flavonol, isoflavone, and isoflavanone) was found to comprise the major constituents, particularly in the EA and 50% MeOH fractions. The clitorienolactones, presently unique to the species, were present in both the free and glycosylated forms in the roots. Both the EA and 50% MeOH fractions displayed moderate effects on the stress-induced zebrafish model, significantly decreasing freezing duration and elevating the total distance travelled and average velocity, 72 h post-treatment. The results of the present study provide further evidence that the basis for the use of C. ternatea roots in traditional medicine to alleviate brain-related conditions, such as stress and depression, is attributable to the presence of clitorienolactones and the isoflavonoidal constituents.